Mapping International Journalism in Post-Soviet Russia: Global Trends vs. National Context - Litvinenko, Anna Alexandrovna; Smoliarova, Anna Sergeevna; Bekurov, Ruslan Viktorovich; Puiy, Anatoli Stepanovich; Glinternik, Eleonora Michailovna (International Review of Management and Marketing, 2015)
Since the beginning of 1990s international journalism in the world is faced with new challenges due to a variety of factors, i.e. technology, globalization and economic crisis in media (Sambrook, 2010). In Russia transformation of international journalism is complicated by the existence of the strong Soviet legacy in the field of foreign reporting and the co-existence of different journalism cultures within one media system. In this paper the authors aim to provide an analysis of the current state of the international journalism in Russia, based on the results of a survey among editors of the leading media outlets as well as among foreign reporters of Russian media and teachers of international journalism at the Russian universities. The results of the study show the existence of cleavage in understanding of functions of foreign reporting between journalists of pro-state and liberal media outlets as well as the overall concern of professionals about the sustainability of international journalism in Russia and abroad. Keywords: international journalism, Russia, global journalism, media crisis, foreign reporting JEL Classifications: D83; I29; Z00; Z13